THE EFFECT OF ALUMINUM STRESS ON RICE VARIETIES AT THE EARLY VEGETATIVE STAGE IN NUTRIENT CULTURE MEDIA: EFEK CEKAMAN ALUMINIUM TERHADAP VARIETAS PADI PADA TAHAP VEGETATIF AWAL DI MEDIA KULTUR HARA - Oktatora, Emilia; Feriadi; Junainah; Hegar Nurjannah; Waliah Nur Rahayu (Jurnal Agro Indragiri, 2025)
This study aims to determine the effect of aluminum stress on rice varieties during the early vegetative phase using a nutrient culture medium. This research employs a completely randomized design with two treatment factors: rice varieties and aluminum concentration. The variety factor consists of Rindang 1, Situ Patenggang, Towuti, Inpago 8, Inpara, and Inpago 10, and the aluminum concentration is 0 ppm and 250 ppm. Rice seeds are germinated for three days. The seeds that have been germinated are then planted in Kimura B nutrient culture media. The condition of the planting media is Kimura B 100% and pH 5.5, and this is maintained until day 21 when the first sampling is conducted. Then, the solution is replaced with a new one using Kimura B 100% nutrient culture media and pH 3.5, along with the addition of 250 ppm aluminum, and this is done until day 28 when the second sampling is conducted. The same procedure is repeated until day 35 when the third sampling is conducted. The analysis results show that the application of 250 ppm aluminum stress significantly affects all rice varieties. In the variables of plant height and root length, the Rindang 1 variety has the highest average values, namely 178.17 cm and 92.12 cm, respectively. Meanwhile, for the variable of leaf count, the variety with the highest average value is Towuti, which is 28.60 leaves. Keyword: Aluminium, Nutrient Culture, Rice, Vegetative